Six new species of Dasyhelea (Insecta, Diptera, Ceratopogonidae) from Patagonia - Díaz, Florentina (2011)
Six new species of Dasyhelea Kieffer, 1911 from Argentinean and Chilean Patagonia are described and illustrated based on adults. Five of these species do not belong to any of the recognized groups found in the Americas. The remaining one, Dasyhelea pabloi sp. nov. is a typical member of the leptobranchia group and is the first record of a species from this group found in the Neotropical region.